THE IMPLEMENTATION OF SMART CITY IN CREATING INNOVATIONS OF PUBLIC SERVICES BY REGIONAL GOVERNMENTS (CASE STUDY OF BANDUNG CITY AND MAKASSAR CITY) - Widuri Wulandari; Siti Munawaroh (Jurnal Caraka Prabu, 2020)
In order to make improvements in public services, the City Government of Bandung and Kota Makassar implement Smart City, and it is also in accordance with the directions of the Kementerian Pendayagunaan Aparatur Negara & Reformasi Birokrasi provide quality services that satisfy the needs of society in the fields of education, health, housing, and so forth. Local governments must also work creatively and innovatively to improve accountability, transparency, and responsiveness by utilizing information technology. The focus of this study is to compare the Government of Bandung with Makassar City in running Smart City in order to implement the innovation of public services. As a method for this research, a qualitative analysis is used, so that the phenomena or situations in the field can be realistically and systematically explained in detail while using the review literature from previous research. The Governments of Bandung City and Makassar City have shown to be successful areas with the implementation of Smart City. Both cities have received many awards for providing innovative services of high quality in spite of the fact that Makassar city started relatively late with implementing Smart City. Although they have been successful so far, the innovation of public services in these two cities will still have to be improved, so that a larger part of society will be able to profit from them. It takes a deep commitment on the part of the local authorities in order to be able to implement Smart City that creates an innovative programme. Smart City's implementation is a solution for creating good governance and makes improvements across multiple sectors of society. Moreover, Smart City sustains community activities and also provides easy access to information made by local governments. Keywords: Smart City, Innovation, Public Service